The association between age at diagnosis of type 2 diabetes and albuminuria in Chinese adults: A nationwide population study. Issue 12 (27th July 2021) - Wu, Shujing; Zhao, Zhiyun; Liu, Shanshan; Li, Mian; Wang, Tiange; Wang, Shuangyuan; Xu, Min; Chen, Yuhong; Dai, Meng; Zhang, Di; Yu, Xuefeng; Tang, Xulei; et al.
Abstract: Background: Type 2 diabetes is increasingly diagnosed at a younger age worldwide and in China. Limited data are available regarding the association between age at diabetes diagnosis and risks of albuminuria. This study sought to examine the independent effect of age at diagnosis of type 2 diabetes on the risk of albuminuria. Methods: We used data from a nationwide multicenter study with 207 961 participants in mainland China. Age, sex, and study site were matched for 31 366 screen‐detected type 2 diabetes cases and 31 366 normal controls. Age, sex, study site, and diabetes duration were matched for 7490 self‐reported type 2 diabetes cases and 7490 normal controls. Risks of having albuminuria in matched type 2 diabetes vs controls were examined using multivariable logistic regression analysis in strata of age at diabetes diagnosis. Results: Although the absolute rate of albuminuria is higher in older adults, the odds ratio of albuminuria in type 2 diabetes vs matched controls decreased with increasing age at diagnosis. For participants with diabetes diagnosed at an age of <50, 50 to 59, 60 to 69, or ≥70 years, the multivariable adjusted risk of albuminuria increased by 81%, 60%, 45%, and 33% for screen‐detected diabetes, and 135%, 121%, 90%, and 58% for self‐reported diabetes compared with their normal controls, respectively. Conclusions: A younger age at diagnosis of type 2 diabetes is associated with a more significantly elevated risk of albuminuria than an older age at diagnosis in Chinese adults. Abstract : Highlights A younger age at diagnosis of type 2 diabetes is associated with a more significantly elevated risk of albuminuria than an older age at diagnosis in Chinese adults, after fully excluding the confounding effect of actual age or diabetes duration. Young adults diagnosed with diabetes were more likely to have an unfavorable metabolic profile compared with normal controls. The age at diabetes diagnosis should be considered when evaluating the risk of developing albuminuria in diabetes patients. 摘要: 背景: 2型糖尿病的诊断年龄在全球及中国呈年轻化的趋势。目前较少研究糖尿病诊断年龄与白蛋白尿患病风险的相关性。本研究拟探讨糖尿病诊断年龄是否为白蛋白尿风险相关的独立危险因素。 方法: 我们使用了来自中国大陆207961名研究对象的全国多中心研究数据。从年龄、性别和研究中心匹配的非糖尿病人群中随机选择正常对照, 另外对已诊断糖尿病患者的病程进行匹配, 最终共有31366 名新诊断2型糖尿病患者和 31366名正常对照, 及7490名已诊断2型糖尿病和7490名正常对照纳入分析。使用多元Logistic回归分析在不同糖尿病诊断年龄层中2型糖尿病患者与正常对照患白蛋白尿的风险。 结果: 虽然年龄越大, 白蛋白尿患病风险越高, 但是2型糖尿病患者与正常对照组白蛋白尿的比值比随着诊断年龄的增加而降低。与正常对照组相比, 年龄 <50、50‐59、60‐69 或≥70 岁诊断为糖尿病的患者经过多变量校正后白蛋白尿风险仍然增加, 新诊断糖尿病分别增加了 81%、60%、45% 和 33%, 已诊断糖尿病分别增加了 135%、121%、90% 和 58%。 结论: 在中国成人中, 2型糖尿病诊断年龄越低, 其白蛋白尿风险升高越明显。